If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -10 = 29 Reorder the terms: -10 + y = 29 Solving -10 + y = 29 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + y = 29 + 10 Combine like terms: -10 + 10 = 0 0 + y = 29 + 10 y = 29 + 10 Combine like terms: 29 + 10 = 39 y = 39 Simplifying y = 39
| 8x-5x=30 | | 8/24=2/n | | 3(k+13)-17=-2 | | n=5p+28+4 | | 3(z+3)=7+3z-6z | | -2(2k-5)=10 | | -19=13-8y | | 3f-8=10f+9-8f | | y^4-3y^2-2y=0 | | n^2-34n+64=0 | | 2x^5+6x^4-4x^2=0 | | 1/4x-3/5=1 | | 8.1=5n-6.4 | | 6py/-5y | | -11w+w=-10 | | -2(p-10)+11=5 | | (x^2+8x)+16=25 | | 2(3x+4)=-16 | | -3d+-d=-20 | | 21k^3-18k^2+7k-6=0 | | 6x^3+15x^2-16x-40=0 | | -10+11u=2+8u | | 2y+-7=19 | | -(-5n+7)-1=2(n+5) | | -6m+18=-8m-20 | | -2=m-16/-1 | | (-0.2)(-0.58)= | | (x+5)(6x-7)=0 | | 7(7x+6)-x=8(4+6x) | | 3k=2k-16 | | f(x)=(2x-1)(x+2)(x+3) | | (7x-1)(x-7)=0 |